UNIVERSALITAS DAN PARTIKULARITAS HAK ASASI MANUSIA DALAM UNDANG-UNDANG NOMOR 1 TAHUN 1974TENTANG PERKAWINAN - Afif Hasan Rifa’i (Universitas Sains dan Teknologi Komputer, 2024)
The human rights are fundamental of human rights or the fundamental rights that existing in human, it’s called the human rights. The human rights are basic of human rights or the rights of human subjects brought from birth as a gift / gift of God. The human rights are fundamental in nature and it’s a natural rights that cannot be separated in human life. Marriage is a basic of human rights and their rights to form family in marriage. The particularities in the Marriage Act which regulates of marriage will result in the universality and particularity of human rights in the regulation of marriage in Indonesia. Universality and particularity of human rights in Law No. 1 Year 1974 on Marriage. So this study can answer the question about how the universality of human rights in Law No. 1 Year 1974 on Marriage and how the particularity of human rights in Law No. 1 Year 1974 on Marriage.